Exploring English Learning Experiences among Health Administration Students: Challenges, Role-Play, and Digital ReadinessExploring English Learning Experiences among Health Administration Students: Challenges, Role-Play, and Digital Readines - Ariani Rosadi; Lubis Hermanto; Muhammad Wardhani; Hanafi Hanafi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
a